2023
DOI: 10.3390/ijerph20064711
|View full text |Cite
|
Sign up to set email alerts
|

Inherited Epigenetic Hallmarks of Childhood Obesity Derived from Prenatal Exposure to Obesogens

Abstract: Childhood obesity has reached epidemic levels in developed countries and is becoming a major cause for concern in the developing world. The causes of childhood obesity are complex and multifactorial, involving the interaction between individual genetics and environmental and developmental factors. Among the environmental factors, there is a growing interest in understanding the possible relationship between the so-called environmental obesogens and the development of obesity in children. Exposure to these obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…Excess weight, nutrient deficiency, excessive weight gain, and exposure to obesogenic environments during pregnancy subject the sperm, ovum, and placenta to inflammation, oxidative stress, lipid accumulation, and insulin resistance, in addition to altering the epigenetics of breast milk and altering the mother’ energy and glucose metabolism. 9 , 30 …”
Section: Data Synthesismentioning
confidence: 99%
“…Excess weight, nutrient deficiency, excessive weight gain, and exposure to obesogenic environments during pregnancy subject the sperm, ovum, and placenta to inflammation, oxidative stress, lipid accumulation, and insulin resistance, in addition to altering the epigenetics of breast milk and altering the mother’ energy and glucose metabolism. 9 , 30 …”
Section: Data Synthesismentioning
confidence: 99%
“…Early life (especially the first 1000 days) represents a critical window for prevention, since it is then that nutritional and exercise patterns, and growth trajectories are set 2 5 8 9. But prevention is difficult given the potent obesogenic environments in which many children grow up and the influence of social determinants at many levels, from family to society at large 5 10. In fact, obesity is linked to poverty and disadvantage (in high-income countries) 11–13.…”
Section: The Challenge Of Obesitymentioning
confidence: 99%
“…The greater susceptibility to pollutants in early childhood is most likely due to the fact that young children's physiological detoxification mechanisms for the removal of xenobiotics from the body are not yet fully developed, giving rise to various diseases, including metabolic disorders such as obesity. In particular, a growing body of evidence has shown that some chemical toxins, known as "obesogens", are capable of interfering with lipid homeostasis and adipocyte physiology, promoting obesity in children, a pathology that has reached epidemic levels in developed countries [10].…”
Section: Adverse Outcomes Of Environmental Pollutants In Young Childrenmentioning
confidence: 99%
“…Bisphenol A (BPA), which occurs in some food storage containers; • Dioxin, which is mainly produced during production processes involving the burning of specific substances and in the initial stages of waste combustion; Some of these EDCs (e.g., BPA, phthalates or dioxins) are known as obesogens due to their ability to promote obesity [10].…”
mentioning
confidence: 99%